2003
DOI: 10.1111/1468-2435.00234
|View full text |Cite
|
Sign up to set email alerts
|

Migration and the Reproduction of Poverty: The Refugee Camps in Jordan

Abstract: This study examines the link between poverty and migration into and out of camps, using 1999 household survey data on the refugee camp populations in Jordan and a binomial logistic regression. The findings show a clear clustering of poverty in the camps, where about one-third of households are poor. Results from several nested regression models show that in-migration is not the cause of persistent poverty in the camps. On the other hand, human capital variables, especially education, economic activity, and "so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 21 publications
1
22
0
Order By: Relevance
“…The monetary values derived from this question can then be compared with actual household income (resources) after appropriate adjustments for household size and composition, to derive a subjective poverty line. 26 Recent studies have found this subjective poverty line similar to those that are calculated using traditional, ''objective'' methods. 27 If proved to be a robust approach to determine minimum living standards, the MIQ could significantly reduce the time, effort and resources needed to establish poverty lines in the future.…”
Section: Economic Povertymentioning
confidence: 51%
“…The monetary values derived from this question can then be compared with actual household income (resources) after appropriate adjustments for household size and composition, to derive a subjective poverty line. 26 Recent studies have found this subjective poverty line similar to those that are calculated using traditional, ''objective'' methods. 27 If proved to be a robust approach to determine minimum living standards, the MIQ could significantly reduce the time, effort and resources needed to establish poverty lines in the future.…”
Section: Economic Povertymentioning
confidence: 51%
“…Most of the Palestinians in Jordan were granted citizenship (Fagen, 2009). Despite Palestinian refugees in Jordan have free access to public schooling, wide range of job opportunities, and free movement (with Jordanian's official travel documents), there are clear differences in life standards between those who live in camps and those who live out camps (Khawaja, 2003). Unlike other Arab countries, such as, Egypt, Iraq, Lebanon, and Syria which offer Palestinians special refugee travel documents and residency permits, Jordan was the only Arab country to grant Palestinian refugees Jordanian citizenship (Shiblak, 1996).…”
Section: Jordan: Long History With Protracted Refugeesmentioning
confidence: 99%
“…Among the studies that we retrieved on refugee poverty in temporary host countries is a study by Khawaja (2003) in Jordan. In this study, 60% of the refugees who were surveyed in 12 refugee camps said they did not have enough money to make ends meet.…”
Section: State Of Knowledge On Refugee Povertymentioning
confidence: 99%
“…The combined lack of physical and social assets and limited resources in host countries puts refugees in vulnerable positions and prone to experience multiple deprivations. While studies on refugees' poverty are scarce, they affirm high rates of poverty among some groups of refugees (Alloush, Gonzalez, Gupta, Rojas, & Taylor, 2016;Chaaban, Seyfert, Salti, & El Makkaoui, 2013;Hejoj, 2007;Khawaja, 2003).…”
mentioning
confidence: 99%